EFFECT OF EXTENDER AND DILUTION RATIO ON THE SPERM MOTILITY, VIABILITY, AND EGGS FERTILITY OF CLARIAS BATRACHUS, LINNAEUS 1758 (PISCES: CLARIIDAE): EXTENDER FOR WALKING CATFISH SPERM - Handayani, Luvi S; Maulida, Siti; Eriani, Kartini; Fadli, Nur; Kocabas, Filiz K; Kocabas, Mehmet; Siti-Azizah, Moh N; Muchlisin, Zainal A. (Polish Journal of Natural Sciences, 2024)
Refrigeration is a simple preservation technique for the short-term storage of fish sperm. The suitable extender and dilution ratio are crucial during this process. Therefore, this study aims to determine the type of extender and the best dilution ratio for preserving walking catfish Clarias batrachus sperm at a refrigeration temperature of 4 °C. The study employed a completely randomized design with two factors, each consisting of 6 treatments and 3 replications. The experiments were divided into 2 stages: the first stage tested several types of extenders, namely tap water, Ringer's solution, physiological solution, Alsever's solution, urea solution, and glucose base solution, all at the same dilution level of 1:20 (sperm:extender, v/v). The second stage examined various levels of sperm dilution ratios, namely 1:10, 1:20, 1:30, 1:40, 1:50, and 1:60 (sperm:extender, v/v). The samples were stored at a refrigerated temperature of 4 °C. Furthermore, motility and viability were monitored at 24-hour intervals for 144 hours, and on the final day of the experiment, the preserved sperm was used for fertilization. The ANOVA test showed that the extender and dilution ratio significantly affected the motility and viability of the spermatozoa and egg fertility (P<0.05). The quality decreased after preservation for 144 hours at 4 °C, but after being diluted with Ringer solution at a ratio of 1:40 (sperm:extender, v/v), it produced better results than other extenders at all dilution ratio levels. Therefore, it is recommended that Ringer's solution at a dilution ratio of 1:40 is suitable for preserving walking catfish C. batrachussperm at a refrigerated temperature of 4 °C.